Impact of the Level of Disclosure of Financial Information on the Pricing of Shares in the Context of Adverse Selection - Lima, Diogo Henrique Silva de; Rodrigues, Jomar Miranda; Silva, César Augusto Tibúrcio; Silva, José Dionísio Gomes da (Review of Business Management, 2012)
Managers know more about the performance of the organization than investors, which makes the disclosure of information a possible strategy for competitive differentiation, minimizing adverse selection. This paper’s main goal is to analyze whether or not an entity's level of disclosure may affect the risk perception of individuals and the process of evaluating their shares. The survey was carried out in an experimental study with 456 subjects. In a stock market simulation, we investigated the pricing of the stocks of two companies with different levels of information disclosure at four separate stages. The results showed that, when other variables are constant, the level of disclosure of an entity can affect the expectations of individuals and the process of evaluating their shares. A higher level of disclosure by an entity affected the value of its share and the other company’s. Key words: Informational asymmetry. Adverse selection. Asset pricing. Stock market. Experimental accounting.